Who Pays for the “Social Cost” of Labor? - Avsar, Rojhat B. (International Journal of Humanities and Social Science Research, 2015)
Although the minimum wage is one of the most commonly researched subjects, its treatment by economists has remained inadequate and led to misconceptions regarding its role in modern society. This philosophical piece offers a rebuttal to the conventional merit-based objection to the minimum wage and puts forward alternative lenses through which the moral appeal of the minimum wage should be (re-)evaluated. We argue that our evolutionary heritage can help us demystify the persistent popular support behind the minimum wage laws. In our framework, the minimum wage laws will be viewed as instrumental in meeting the “basic needs” of those who are offering productive contributions. The approach taken in this paper will supplement and modify old institutionalist framework and equip it with proper moral foundations.